Creating Shared Understanding in Product Development Teams How to 'Build the Beginning' - Møller, Louise; Tollestrup, Christian (Springer London : Imprint: Springer, 2013)
Development projects that span different disciplines and groups often face problems in establishing a shared understanding of the project's purpose, deliverables, and direction. Creating Shared Understanding in Product Development Teams: How to 'Build the Beginning' uses research-based cases from TC Electronic, The Red Cross, Daimler AG, and Copenhagen Living Lab to demonstrate one approach to this problem complex. It shows how prototyping specific physical artifacts can function as drivers and focal points for creating the much needed shared understanding. Encompassing both the participant's and the facilitator's point of view, Creating Shared Understanding in Product Development Teams: How to 'Build the Beginning' provides both practical examples and theoretical explanation for the process of creating shared understanding. This book provides a toolbox and a practical guide for planning, executing, and facilitating workshops. The result is a clear outline of how to facilitate the creation of physical artifacts that enables and stimulates communication between team members, users, and stakeholders in order to create shared understanding of projects.